Effects of cooperative learning on students' achievement and attitudes in secondary mathematics - Hossain, Anowar; Ahmad Tarmizi, Rohani (Elsevier, 2013)
The main purpose of this study was to identify the effects of cooperative learning on students’ mathematics achievement and attitudes towards mathematics in selected secondary schools in Bangladesh. A total of 80 students (40 from Boys’ school and the other 40 from Girls’ school) of grade nine participated in this study where quasi-experimental design was administered. Data were analyzed using independent-sample test. The results showed that cooperative learning had significant effects on mathematics achievement and attitudes towards mathematics. It was found that students’ performance in mathematics and attitudes towards mathematics were affected by exposure to the cooperative learning. The findings of this study have shown a great improvement in mathematics achievement and attitudes towards mathematics. Therefore, cooperative learning can be successfully used to promote student’ performance in mathematics in secondary schools in Bangladesh.